IMPLEMENTASI HAK-HAK NARAPIDANA BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2022 SERTA HAMBATAN-HAMBATANNYA DI LEMBAGA PEMASYARAKATAN KELAS IIA KUPANG - Napu, Papy Michael; Leo, Rudepel Petrus; Amalo, Heryanto (Petitum Law Journal, 2023)
Implementation of the rights of correctional inmates is a continuous development effort. This lack of attention to the fulfillment of prisoners' rights is closely related to prisoner development and can result in a sub-optimal process of prisoner development which fails in the initial objectives of the Correctional System. The main problems in this research are: (1) How are prisoners' rights implemented in the Kupang Class IIA Penitentiary based on Law Number 22 of 2022 concerning Corrections? (2) What are the obstacles in implementing prisoners' rights at the Kupang Class IIA Penitentiary? This type of research is qualitative research using a juridical-empirical legal research approach, namely an approach carried out in the field by collecting information by observing and interviewing sources related to the research that will be discussed in this research which was carried out at the Class IIA Correctional Institution Kupang, East Nusa Tenggara Province. The results of this research show that: (1) The implementation of prisoners' rights in the Kupang Class IIA Correctional Institution based on Law Number 22 of 2022 concerning Corrections, in general, can be said to be good, but it still needs to continue to be improved starting from carrying out worship according to religion and trust, receive physical and spiritual care, education, teaching and opportunities to develop potential, health services, information services, counseling, and legal assistance, submit complaints, participate in mass media broadcasts, be treated humanely, receive work safety guarantees and receive social services and accepting and refusing visits and their implementation will continue to be implemented until the prisoner has finished serving his sentence. (2) Obstacles include, among others, a shortage of guard duty personnel, a lack of budget, and a shortage of health and education personnel, in terms of education itself there is no special intellectual officer, even in recruitment, up to now there has been no recruitment for teaching staff, especially intellectual education.